The Effect of Intrinsic and Extrinsic Motivation on Employee Performance - Buana, Nangku; Rahmayati, Rahmayati (Newinera Publisher, 2024)
Knowing how employees of PT. BPRS Puduarta Insani Medan are motivated, both internally and externally, to give their best performance is the driving force of this research. This study involved a total of 21 participants. This study used a quantitative approach and utilized a sampling technique known as saturated sampling. The data collection process involved distributing questionnaires and utilizing a Likert scale as a means to quantify participant responses. This study used SPSS version 26 for data analysis and multiple linear regression. Based on the results of the t-test, both internal and external factors significantly affect worker output. The results showed that, compared to extrinsic motivation, intrinsic motivation has a significant impact on worker output.